Opposing impact of B cell intrinsic TLR7 and TLR9 signals on autoantibody repertoire and systemic inflammation - Jackson, Shaun W. (2014)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by autoantibodies targeting nucleic acid-associated antigens. The endosomal toll-like receptors TLR7 and TLR9 are critical for generation of Abs targeting RNA- or DNA-associated antigens, respectively. In murine lupus models, deletion of TLR7 limits autoimmune inflammation, while deletion of TLR9 exacerbates disease. Whether B cell or myeloid TLR7/TLR9 signaling is responsible for these effects has not been fully addressed. Here, we utilize a chimeric strategy to evaluate the effect of B cell-intrinsic deletion of TLR7 vs. TLR9 in parallel lupus models. We demonstrate that B cell-intrinsic TLR7 deletion prevents RNA-associated Ab formation, decreases production of class-switched Abs targeting non-nuclear antigens and limits systemic autoimmunity. In contrast, B cell-intrinsic TLR9 deletion results in decreased DNA-reactive Ab, but increased Abs targeting a broad range of systemic autoantigens. Further, we demonstrate that B-intrinsic TLR9 deletion results in increased systemic inflammation and immune-complex (IC) glomerulonephritis despite intact TLR signaling within the myeloid compartment. These data stress the critical importance of dysregulated B cell-intrinsic TLR signaling in the pathogenesis of SLE.